College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter P, Prerequisites - Section P.6 - Factoring - P.6 Exercises: 83

Answer

$(t+1)(t^2-t+1)$

Work Step by Step

RECALL: A sum of two cubes can be factored using the formula $A^3+B^3=(A+B)(A^2-AB+B^2)$ The given binomial can be written as: $=t^3+1^3$ The binomial is a sum of two cubes. Factor using the formula above with $A=t$ and $B=1$ to obtain: $=(t+1)(t^2-(t)(1)+1^2) \\=(t+1)(t^2-t+1)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.